Extraction of essential oil -pinene and B-pinene found in spearmint leaves using different solvent at pressure (0.1-11 MPa) and temperature (40 C and 60 C) - Ooi, Chung Cheat (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
The objectives if this project is to study the extraction methods of the heavy components (spearmint oil derivatives) with some solvents such as hexane, chloroform and carbon dioxide respectively. Extraction data obtained would base on the derivatives of yield. The extraction methods are derived and studied would be water-bath, soxhlet and ultrasonic-assisted methods while the high pressure extracted method using CO2 as a solvent would be review aim reference (5). The experimental data obtained be analyzed by using gas chromatography and are compared partially with theoretical data obtained by Peng-Robinson equation of state. Computerized aided programmed are designed and used to re-extract new extractive data from reference (5). Then, the percentage yield of extraction and composition of pinene and pinene among water-bath, soxhlet and ultrasonic-assisted illustrate that ultrasonic-assisted method execute best result. Simulated data for supercritical CO2 extraction are base on mole fraction of component in system CO2 (i)-oil component (j). High mole fraction CO2 was showing that low value mole fraction of oil component. The results show high composition pinene at 60 C, 8000 kPa and 4 hours extraction time while pinene at 60 C, 8000 kPa and 2 hours extraction time